Exploring the integration of live, virtual, and constructive environments in fighter pilot training through Link-16: lessons learned regarding training aspects - Thijssen, D.; Pelt, D.M.; Benthem, G.J. van; Zwaan, S.; Petermeijer, S.M.; Pal, J. van der (Sage Journals, 2025)
Live, Virtual, and Constructive (LVC) training has gained attention as a cost-effective and scalable approach to improve fighter pilot training. Despite its potential, achieving a highly interoperable LVC environment remains a challenge, limiting its widespread implementation in the near future. However, integrating existing technologies and operational datalinks offers opportunities to enhance training effectiveness, even with some limitations in interoperability and interaction. This study investigates the feasibility and benefits of incorporating LVC elements into training scenarios. In October 2023, a synthetic environment combining a virtual fighter and constructive elements was integrated into the large-scale Frisian Flag exercise. Through Link-16 datalink and ultra-high-frequency (UHF) radio connectivity, virtual and live elements exchanged data, allowing the virtual simulator to participate in Offensive and Defensive Counter Air missions alongside live pilots. Post-training evaluations indicated that the virtual and constructive elements positively impacted the training value for live pilots, while pilots operating the virtual simulator also reported benefits, albeit to a lesser extent than in live sorties. This paper focuses on the training outcomes within the context of Frisian Flag and seeks to provide broader insights for diverse training scenarios.